2016
DOI: 10.5665/sleep.5642
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Orexin A Levels and Autonomic Function in Kleine-Levin Syndrome

Abstract: There are lower orexin A levels in the symptomatic phase than in remission and a fall and rise in blood pressure and heart rate, suggesting a role for orexin dysregulation in KLS pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 36 publications
0
20
0
2
Order By: Relevance
“…Potential implication of hypocretins (namely, a decreased cerebrospinal fluid [CSF] level during the hypersomnia period) was reported (Lopez, Barateau, Chenini, & Dauvilliers, ). A recent study in 44 Chinese KLS patients also reported that the CSF hypocretin‐1 levels were 31% lower during relapse (Wang et al, ). In addition to hypocretin neurons, LMOD3 was also found to be expressed in the tuberomammillary locus, locus coeruleus, ventral tegmental area and substantia nigra, as well as in the raphe nucleus, all critically involved in the maintenance of wakefulness.…”
Section: Discussionmentioning
confidence: 93%
“…Potential implication of hypocretins (namely, a decreased cerebrospinal fluid [CSF] level during the hypersomnia period) was reported (Lopez, Barateau, Chenini, & Dauvilliers, ). A recent study in 44 Chinese KLS patients also reported that the CSF hypocretin‐1 levels were 31% lower during relapse (Wang et al, ). In addition to hypocretin neurons, LMOD3 was also found to be expressed in the tuberomammillary locus, locus coeruleus, ventral tegmental area and substantia nigra, as well as in the raphe nucleus, all critically involved in the maintenance of wakefulness.…”
Section: Discussionmentioning
confidence: 93%
“…The psychiatric symptomatology during KLS episodes has been previously described in several studies (Arnulf, Zeitzer, File, Farber, & Mignot, ; Arnulf et al., ; Huang et al., ; Lavault et al., ; Wang et al., ), but has sometimes been based on questionnaires rather than on psychiatric interviews (Arnulf et al., ). It most resembled clinical features of mood disorders and psychotic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The episodes are frequently triggered by infections and separated by asymptomatic periods (Arnulf, Rico, & Mignot, ; Huang et al., ). Behavioural disturbances (hypersexuality, megaphagia or loss of appetite, aggressiveness and regressive behaviour) and psychiatric symptomatology (depressed mood, hallucinations, delusions and psychomotor excitement) are present during episodes in approximately half of patients (Arnulf et al., ; Wang et al., ). However, the characteristics of these symptoms are incompletely known.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos autores consideran una variante cuando se produce asociado al síndrome menstrual [8]. A pesar de haberse encontrado alteraciones en la neuroimagen funcional [13,14] y una orexina A (hipocretina 1) en el límite bajo en el líquido cefalorraquídeo de los pacientes durante los episodios [15], no existe actualmente una prueba diagnóstica.…”
Section: Discussionunclassified